The increasing problem of treatment‐resistant fungal infections: a call for antifungal stewardship programs. (17th March 2021) - Gupta, Aditya K.; Venkataraman, Maanasa; Renaud, Helen J.; Summerbell, Richard; Shear, Neil H.; Piguet, Vincent
Abstract: Antimicrobial stewardship (AMS) programs have been widely recognized among the public health community. These programs focus majorly on bacterial infections, efficient antibiotic use, and measures to curb increasing antibacterial resistance. AMS programs are successfully established around the globe; however, very few include antifungal stewardship (AFS). The increasing incidence of superficial and invasive fungal infections, combined with delayed or inaccurate diagnosis, has contributed to the overprescribing and overuse of antifungal agents. Such increased exposure to antifungal agents may be a reason for the emergence of increasing antifungal resistance among fungal pathogens. With mounting reports of treatment failures and resistant infections, the evidence to support the need for AFS programs is increasing. AFS is an emerging branch of AMS programs that requires global attention and recognition.